Investigating the Association between Ambiguity Tolerance and Vocabulary Knowledge in Iranian EFL Learners - Jowkar, Mehdi; Khajehie, Hassan (Advances in Social Sciences Research Journal, 2017)
Learning a new language can be likened to the exploring of an unknown land, as there are varying ambiguous situations in the learning tasks. Ambiguity tolerance, as an important learning style, can inhibit or facilitate language learning. The present study seeks to unravel how tolerant/intolerant EFL learners are of such ambiguities as well as exploring whether tolerance of ambiguity of EFL learners affects their vocabulary knowledge. The study also aimed to investigate whether there is any gender-related difference in tolerance of ambiguity of EFL learners and whether ambiguity tolerance is somehow associated with self-perceived success of Iranian EFL learners in vocabulary. This study was carried out with 60 freshmen enrolled in the English Language Teaching (ELT) Department of Kazerun Islamic Azad University in Iran. The data collection instruments consisted of the Second Language Tolerance of Ambiguity Scale and the Vocabulary Levels Test. The obtained data were subsequently analyzed descriptively using the SPSS, version 21 software. The results revealed that EFL learners have a moderate level of ambiguity tolerance in foreign language learning and that gender does not have any significant impact on tolerance of ambiguity. It was also found that there is no significant relationship between tolerance of ambiguity and vocabulary knowledge whereas a significant relationship between tolerance of ambiguity and self-perceived achievement in foreign language vocabulary learning was detected. Implications based on the findings are also suggested.